Nesta Pain: The Entangled Media Producer. Issue 1 (2nd January 2020) - Terkanian, Kate; Chignell, Hugh
Abstract : The 'cultural translator' is an individual who expresses the essence of entanglement in their career choices, moving between genres, media, or nations. This article suggests that the BBC producer and writer, Nesta Pain, was such an individual. Over the course of her career, Pain not only wrote and produced radio features and radio dramas but was also a successful journalist and author. She translated her experience in radio production onto the stage and on television by exploiting the different possibilities offered by these visual media—all evidence of her transmedial cultural translation. Further adding to the transgressive nature of her career, was her place as a woman in male-dominated radio production arenas.